Medicare cost reduction in the US: A case study of hospital readmissions and value-based purchasing. (2nd January 2021) - Kocakulah, Mehmet C.; Austill, David; Henderson, Eric
ABSTRACT: The goal of this research paper is to provide a case study of two ACA initiatives focused specifically on Medicare cost reduction: Readmissions Reduction Program (RRP) and Value-Based Purchasing (VBP). The paper discusses generally how the ACA reforms are aimed to reduce Medicare costs through these two cost reduction programs and how hospitals are impacted by the financial penalties associated with these reforms. Through a case study of a Midwestern regional acute care hospital, detailed solutions will be provided on ways to limit financial losses. Additionally, consideration will be given to how much a hospital should weigh its investment in improving program metrics versus the net overall benefit.